2016
DOI: 10.1177/0748233715592992
|View full text |Cite
|
Sign up to set email alerts
|

Formaldehyde exposure inhibits the expression of mammalian target of rapamycin in rat testis

Abstract: Formaldehyde (FA), a ubiquitous environmental pollutant, has long been suspected of causing adverse male reproductive effects. However, the molecular and cellular mechanisms underlying this phenomenon remain elusive. The overall aim of this study is to clarify the role of mammalian target of rapamycin (mTOR) in male reproductive injuries induced by FA exposure, by which we can further understand the molecular mechanism of FA male reproductive toxicity. In this study, immunohistochemistry, Western blotting, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…reported the downregulation of the mTOR/P70S6K1 signalling pathway after PM 2.5 exposure ( Zhang et al, 2019 ), and Fang et al . found that formaldehyde exposure inhibits the expression of mTOR in a dose-dependent manner ( Fang et al, 2015 ). Formaldehyde exposure has been reported to result in DPCs in lymphocytes, which was then shown to be reversed by the FANCD2-participating pathway ( Ren et al, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…reported the downregulation of the mTOR/P70S6K1 signalling pathway after PM 2.5 exposure ( Zhang et al, 2019 ), and Fang et al . found that formaldehyde exposure inhibits the expression of mTOR in a dose-dependent manner ( Fang et al, 2015 ). Formaldehyde exposure has been reported to result in DPCs in lymphocytes, which was then shown to be reversed by the FANCD2-participating pathway ( Ren et al, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…Spermatogenesis, the transformation of spermatogonia into sperm, is a well-orchestrated and precisely-regulated biological process which is strictly regulated by phase-specific gene expression [4, 2931]. Noncoding RNAs such as microRNAs (miRNAs), PIWI-interacting RNAs (piRNAs) and long non-coding RNAs (lncRNAs) are important post-transcriptional regulators of gene expression in multiple stages of spermatogenesis [32, 33].…”
Section: Discussionmentioning
confidence: 99%
“…It is a colorless, highly water soluble, and reactive substance that could rapidly diffuse into many organs and tissues (Tang et al, 2009). Currently, despite many preventive measures taken to reduce FA contaminant, exposure to FA remains one of the most prominent environmental health problems worldwide (Duong et al, 2011; Fang et al, 2016; Han et al, 2015; Tang et al, 2009; Zhou et al, 2006).…”
Section: Discussionmentioning
confidence: 99%